Estimation of wage equations for New Zealand - Joseph Mercante; Penny Mok (New Zealand Government, The Treasury, 2014)
This paper estimates wage equations for New Zealand based on pooled data from the Household Economic Survey (HES) from 2006/07 to 2010/11. Equations are estimated separately for couple men and women, single men and women and sole parents. The results are compared to previous New Zealand estimates using the HES from 1991 to 2001. We estimate wage equations and account for possible sample selection bias. Our estimates of the wage equations are largely comparable to the earlier estimates. We extend the equations to predict wage rates for workers and non-workers by drawing from the estimated wage distribution. We find that sample selection is significant for married men, single women and sole parents but not significant for married women and single men. Overall, we find that wage rates are positively related to age, education and experience but the wage rates are generally lower for non-Europeans and for people living outside Auckland.
Keywords: J21; J31; 330; wage rate; labour supply; selection bias; wage prediction; Arbeitsangebot; Lohnniveau; Systematischer Fehler; Prognoseverfahren; Neuseeland